Bioaccumulation of triclosan and triclocarban in plants grown in soils amended with municipal dewatered biosolids. (3rd March 2014) - Prosser, Ryan S.; Lissemore, Linda; Topp, Edward; Sibley, Paul K.
Abstract Biosolids generally contain the microbiocidal agents triclosan (TCS) and triclocarban (TCC) that are persistent during wastewater treatment and sorp to organic material. The present study investigated the concentration of TCS in tissues of radish, carrot, and soybean grown in potted soil amended with biosolids. Highest mean concentrations of TCS in radish, carrot, and soybean root tissue midway through the life cycle were 24.8 ng/g, 49.8 ng/g, and 48.1 ng/g dry weight, respectively; by the conclusion of the test, however, concentrations had declined to 2.1 ng/g, 5.5 ng/g, and 8.4 ng/g dry weight, respectively. Highest mean concentrations of TCS in radish and carrot shoot tissue were 33.7 and 18.3 ng/g dry weight at days 19 and 45, respectively, but had declined to 13.7 ng/g and 5.5 ng/g dry weight at days 34 and 69, respectively. Concentration of TCS in all samples of soybean seeds was below method detection limit (i.e., 2.8 ng/g dry wt). The present study also examined the concentration of TCS and TCC in edible portions of green pepper, carrot, cucumber, tomato, radish, and lettuce plants grown in a field amended with biosolids. Triclosan was detected only in cucumber and radish up to 5.2 ng/g dry weight. Triclocarban was detected in carrot, green pepper, tomato, and cucumber up to 5.7 ng/g dry weight. On the basis of the present study and other studies, we estimate that vegetable consumption represents less than 0.5% of the acceptable daily intake of TCS and TCC. These results demonstrate that, if best management practices for land application of biosolids in Ontario are followed, the concentration of TCS and TCC in edible portions of plants represents a negligible exposure pathway to humans. Environ Toxicol Chem 2014;33:975–984. © 2014 SETAC